The Biophysical Modelling of the Systems Theory - Vincze, Janos; Tiszay, Gabriella Vincze- (Jour Med Resh and Health Sci, 2023)
Modelling in simplest formulation can be conceived as a sharp polarized inquiry of the respective phenomenon. A fortunate model describes the given momentary acquirements but beyond this it enables assumptions which can be then translated into the language of the experiment and on this basis you can arrange certain new exprimental conditions and situations. The biologist has to abstract parts of the biological process substantial from the point of view of the model and has to select those essential points the physicist willingly accepts and in which he will be ready to collaborate. Moreover, if members of a model family can be transferred into each other unequivocally enough then we can speak about a theory-forming model system. The biophysical approximation of the life processes leads always to the application of some kind of physical model. The biophysical approximation of the life processes leads always to the application of some kind of physical model. The system is a fundamental concept which is not defined. For practical reasons, let’s circumscribe the concept of the system more exactly as such an arrangement of the constituents which serves to reach the concrete purpose according to a certain programme. The hierarchy of the systems will be built up according to a spiral line expanding in breadth and depth towards the infinity.